2003
DOI: 10.1051/0004-6361:20031463
|View full text |Cite
|
Sign up to set email alerts
|

Bright OB stars in the Galaxy

Abstract: Abstract. We study mass-loss and wind momentum rates of 29 Galactic O-type stars with luminosity classes I, III and V by means of a pure Hα profile analysis and investigate to what extent the results compare to those originating from a state-ofthe-art, complete spectral analysis. Our investigation relies on the approximate method developed by Puls et al. (1996) which we have modified to account for the effects of line-blanketing. Effective temperatures and gravities needed to obtain quantitative results from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
201
2
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(225 citation statements)
references
References 53 publications
17
201
2
5
Order By: Relevance
“…The stellar parameters (effective temperatures and radii) of an O star sample were derived using the model atmospheres with line blanketing Markova et al 2004;Martins et al 2005). Stellar masses were obtained using evolutionary tracks either by ourselves (using Schaller et al 1992 tracks) or by Martins et al (2005).…”
Section: Studied Model Starsmentioning
confidence: 99%
“…The stellar parameters (effective temperatures and radii) of an O star sample were derived using the model atmospheres with line blanketing Markova et al 2004;Martins et al 2005). Stellar masses were obtained using evolutionary tracks either by ourselves (using Schaller et al 1992 tracks) or by Martins et al (2005).…”
Section: Studied Model Starsmentioning
confidence: 99%
“…Note that the parameters derived by Repolust et al (2004), Markova et al (2004), and Martins et al (2005) were obtained using blanketed model atmospheres, i.e., they should be more reliable than the older ones. Stellar masses were obtained using evolutionary tracks (Schaller et al 1992).…”
Section: Test Starsmentioning
confidence: 99%
“…However, recent observational studies Markova et al 2004) indicate that the situation is probably more complicated. They concluded that there are two different wind momentum-luminosity relationships for supergiants (or, probably more correctly, for stars with the Hα line in emission), and for other stars (mainly for giants and mainsequence stars).…”
Section: Wind Momentum Luminosity Relationshipmentioning
confidence: 99%